'A new discovery' of Charles Hoole: method and practice in seventeenth-century English education. Issue 1 (2nd January 2019) - Gianoutsos, Jamie
ABSTRACT: This article offers the first modern explication of the educational writings of Charles Hoole (1610–1667), arguing that his writings offer significant insight into the educational aims and methods of school instructors in seventeenth-century England. From attending to the needs of slow learners, to promoting learning games, to emphasising that children should be treated as rational actors, Hoole's A New Discovery of the Old Art of Teaching Schoole (1660) fused theoretical expositions on the aims of education with practical recommendations to schoolmasters on how to succeed in these aims. Hoole's writings, as well as the earlier humanist pedagogical treatises of his peers, demonstrate that early and mid-seventeenth-century schoolmasters were already discussing and potentially implementing a number of educational initiatives that historians have traditionally credited to John Locke and later eighteenth-century educational theorists.